IMPLEMENTASI LANDASAN KONVENSIONAL DAN YURIDIS DALAM PENYELENGGARAAN PENDIDIKAN INKLUSI DI SEKOLAH DASAR KABUPATEN BUNGO - Istikhanah, Anisa Sari; sary, Yolanda Lupita; Andriani, Opi (Jurnal Pendidikan Vokasi dan Seni, 2023)
Elementary schools with inclusive education programs are a challenge for school principals and teachers in educational institutions. Inclusive education in elementary schools needs to get more attention considering that elementary school students still need intensive attention from educators coupled with the presence of students with special needs, of course it is not easy to achieve learning goals. The aim of this research was to observe and describe the phenomena that occur in the implementation of inclusive education in elementary schools. This research uses a qualitative approach with descriptive methods, describing facts or circumstances related to the implementation of conventional and juridical foundations in the implementation of inclusive education in elementary schools in Bungo district. The research results show that there is a mismatch in educational services and facilities for ABK, such that services should be adjusted to the individual needs of children according to their abilities. As a solution, researchers suggest that schools, related agencies and the government pay further attention so that the educational rights of every child, including ABK, can be fulfilled optimally in accordance with applicable regulations.